Magnetron-sputtered Polytetrafluoroethylene-stabilized Silver Nanoisland Surface for Surface-Enhanced Fluorescence - Šubr, Martin; Praus, Petr; Kočišová, Eva; Procházka, Marek; Štěpánek, Josef; Kuzminova, Anna; Kylián, Ondřej; Sureau, Franck (Nanomaterials (Basel, Switzerland), 2020)
Surface-enhanced fluorescence (SEF) requires the absorption/emission band of the fluorophore, the localized surface plasmon resonance (LSPR) of the nanostructure and the excitation wavelength to fall in the same (or very close) spectral range. In this paper, we monitor the SEF intensity and lifetime dependence of riboflavin (vitamin B2) adsorbed on a spacer-modified Ag substrate with respect to the thickness of the spacer. The substrates were formed by silver nanoislands deposited onto magnetron-sputtered polytetrafluoroethylene (ms-PTFE). The spacer was formed by the ms-PTFE layer with the thickness ranging from ~5 to 25 nm. The riboflavin dissolved in dimethylsulfoxide (DMSO) at a 10 µM concentration forms, at the ms-PTFE surface, a homogeneous layer of adsorbed molecules corresponding to a monomolecular layer. The microspectroscopic measurements of the adsorbed layer were performed through a sessile droplet; our study has shown the advantages and limitations of this approach. Time-resolved fluorescence enabled us to determine the enhanced fluorescence quantum yield due to the shortening of the radiative decay in the vicinity of the plasmonic surface. For the 5 nm ms-PTFE layer possessing the largest (estimated 4×) fluorescence enhancement, the quantum yield was increased 2.3×.
Keywords: riboflavin; surface-enhanced fluorescence (SEF); lifetime; enhancement factor; time-resolved